Handbook of public opinion research - Donsbach, Wolfgang; Donsbach, Wolfgang, 1949-; Traugott, Michael W. (Thousand Oaks, CA : SAGE, 2008)
An indispensable resource for both practitioners and students alike, the handbook brings together a review of what public opinion is, what role it has in a society, how it changes and by what it is affected, how it can be measured and what impact it has.
I: History, philosophy of public opinion and public opinion research -- The nature of public opinion -- The development of public opinion research -- II: Theories of public opinion formation and change -- Formation of opinion -- Dynamics of public opinion -- III: Methodology -- The design of surveys -- Measurement of public opinion -- IV: The social and political environment of public opinion research -- The status of public opinion research -- Uses and effects of public opinion research -- V: Special fields of application.
Includes bibliographical references.
Keywords: Public opinion polls; Public opinion